Parenting Interventions for Indigenous Child Psychosocial Functioning: A Scoping Review. (May 2017) - Macvean, Michelle; Shlonsky, Aron; Mildon, Robyn; Devine, Ben
Objectives: To scope evaluations of Indigenous parenting programs designed to improve child psychosocial outcomes. Methods: Electronic databases, gray literature, Indigenous websites and journals, and reference lists were searched. The search was restricted to high-income countries with a history of colonialism. Results: Sixteen studies describing evaluations of 13 programs were found. Most were controlled studies from United States and Australia, targeting child social, emotional, behavioral and mental health outcomes, and these were delivered to groups of parents. Program content focused most often on child development and learning, child behavior management, and parent–child interactions. Some studies reported improvements in child and parent outcomes, though the majority used self-report measures and some were noncontrolled studies. Conclusions: This scoping review provides the first known map of evaluations of programs targeting parents of Indigenous children. There were few rigorous evaluations of effectiveness. A rigorous systematic review is needed to evaluate the strength and extent of these findings.